Financing the green transition. The role of macro-economic policies in ensuring a just transition - Braga, João Paulo; Ernst, Ekkehard (Frontiers in Climate, 2023)
The transition to a green economy requires significant resources, both from private investors and public policy makers with important implications for employment and living standards. This paper argues that green macro-economic policies are essential in accelerating the transition through three channels: they can strengthen the price signals from externality pricing; they can mobilize additional public and hybrid funding for green transition projects; and they can soften the social and labor market impact of the transition for those workers currently still employed in polluting industries. The paper provides an overview of the main fiscal, monetary and financial market policies that can help provide the necessary fund for a successful transition. It highlights different trade-offs regarding instrument choice and policy outcomes, notably regarding the need to achieve a transition that is both ecological and socially sustainable. We provide an overview of current policy choices and document their economic, social and ecological outcomes. In particular, we demonstrate that the proper use of price regulation and financial instruments—carbon taxes, cap-and-trade schemes, green bonds, nature-based capital—can mobilize additional resources that can be usefully invested to ensure a socially just transition.